Evaluation of Mangroves Effectiveness in Strengthening Coastal Bund Using Geophysical Method (Non-Destructive Testing) at Tanjong Laboh, Batu Pahat, Johor - Mohammad Razi, Mohd Adib; Rahmat, Siti Nazahiyah; Jamal, Mohamad Hidayat; Tajul Baharuddin, Mohamad Faizal; Wang, Mo; Husin, Tariq Mubarak (International Journal of Integrated Engineering, 2023)
In recent years, mangrove forests have rapidly become an endangered ecosystem in the world. On the coastal shorelines, the saltwater intrusion (SI) phenomenon is a main concern that can affect the quality of water. The saltwater intrusion might occur due to sea level rise, and extreme natural disasters along with changes in mangrove ecosystem distribution. The purpose of this research is to evaluate the effectiveness of mangroves for strengthening coastal bunds in Tanjong Laboh, Batu Pahat, Johor. By using the non-destructive geophysical method, the presence of saltwater intrusion and subsurface profile of the survey line in the coastal area with and without mangroves was determined. The coastal bund conditions with and without mangroves were also compared in order to evaluate how the mangrove forest acts as coastal protection. The result shows that the resistivity values of 0.1 to 1.0 ohm.m are more dominant in the mangrove bund area than in the engineered coastal bund and rock outcrop areas. The saltwater intrusion integrity map was produced from the 2D subsurface image profiles for both survey lines. The comparison of the coastal bund conditions for two different scenarios, which with and without mangroves, has shown that the coastal bund without the mangroves experienced cracking and erosion compared to the coastal bund with the presence of mangroves. This indicates the importance of mangroves in protecting the coastal regions.